Kristologi Dalam Injil Yohanes : Yesus Sebagai Jalan, Kebenaran dan Hidup - Nino Sampe T Sitohang; Marliana Lase; Suang Manik; Johanes GB Panjaitan (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2025)
The understanding of Christology among Christians is often ambigued. Some believe that Jesus only had a divine nature without a human nature, while others believe that Jesus was just an ordinary man. Therefore, it is very important for believers to have a proper understanding of Jesus Christ, which is based on the truth of God's Word, so that their faith is firm and in accordance with the teachings of the Bible. In this article “Christology in the Gospel of John: Jesus as the Way, the Truth, and the Life” can include the understanding that the Gospel of John emphasizes the identity of Jesus as the only way to salvation, the absolute truth, and the source of eternal life. In this context, Jesus is presented as the link between humanity and God, offering a deep understanding of spiritual and existential relationships. Through His statements, such as “I am the way, the truth, and the life,” the Gospel of John describes Jesus' mission of saving mankind and reveals God's loving nature.